The IMPACT study: A clustered randomized controlled trial to assess the effect of a referral algorithm for axial spondyloarthritis. - Maha Jamal; Amber M Korver; Martijn Kuijper; Deirisa Lopes Barreto; Cathelijne W Y Appels; Anneke P L Spoorenberg; Bart W Koes; Johanna M W Hazes; Lonneke van Hoeven; Angelique E A M Weel (PLoS ONE)
Background A substantial number of patients with chronic low back pain (CLBP) have axial spondyloarthritis (axSpA), but early recognition of these patients is difficult for general practitioners (GPs). The Case Finding Axial Spondyloarthritis (CaFaSpA) referral strategy has shown to be able to identify patients with CLBP at risk for axSpA, but its impact on clinical daily practice is yet unknown. Objective To assess the effect of the CaFaSpA referral strategy on pain caused by disability in primary care patients with CLBP. Methods Within this clustered randomized controlled trial 93 general practices were randomized to either the CaFaSpA referral model (intervention) or usual primary care (control). In each group primary care patients between 18 and 45 years with CLBP were included. The primary outcome was disability caused by CLBP, measured with the Roland Morris Disability Questionnaire (RMDQ) at baseline and four months. Secondary outcome was the frequency of new axSpA diagnosis. Descriptive analyses were performed, and a linear mixed-effects model was used. Results In total 679 CLBP patients were included of which 333 patients were allocated to the intervention group and 346 to the control group. Sixty-four percent were female and mean age was 36.2 years. The mean RMDQ score at baseline was 8.39 in the intervention group and 8.61 in the control group. At four months mean RMDQ score was 7.65 in the intervention group and 8.15 in the control group. This difference was not statistically significant (p = 0.50). Six (8%) out of the 75 finally referred patients, were diagnosed with axSpA by their rheumatologist. Conclusions The CaFaSpA referral strategy for axSpA did not have an effect on disability after four months caused by CLBP. However, the strategy is able to detect the axSpA patient within the large CLBP population sufficiently. Trial registration number: NCT01944163, Clinicaltrials.gov.